On some Species of Rhododendron from Subansiri District, North East Frontier Agency - Sastry, A. R. K.; Kataki, S. K. (Indian Forester, 2005)
Rhododendron arizelum, R. peramoenum and R. stenalum are recorded as new in Subansiri District.